Digital transformation in commercial banks: Unraveling the flow of Industry 4.0 - Thiago Felipe; Rui Torres de Oliveira; Agnes Toth-Peter; Shane Mathews; Uwe Dulleck (Digital Business, 2025)
This study investigates the strategies employed by commercial banks during their digital transformation, particularly regarding the integration of Industry 4.0 technologies. A systematic literature review of 287 articles was conducted to identify strategies at micro, meso, and macro levels. At the micro level, three key strategies emerged: value co-creation, security, and inclusion, aiming to enhance customer experience, secure data, and improve digital accessibility. At the meso level, banks adopt agile organisational structures, automation, and expand digital platforms to optimise internal processes and foster external collaborations. At the macro level, strategies include establishing fully digital banks, incorporating digital features into traditional operations, or collaborating with other stakeholders to innovate business models. A conceptual framework is presented to illustrate the dynamic interaction between these levels, emphasising the importance of a holistic approach for successful digital transformation. The research connects its findings to theories of general-purpose technology and dynamic capabilities. Implications highlight the need for overcoming challenges such as legacy systems, regulatory complexities, and internal resistance. These findings offer valuable insights for banks implementing Industry 4.0 technologies, with a focus on strategic alignment, organisational readiness, and technological innovation.
Keywords: 650; Banking; Commercial banks; Digital transformation; Dynamic capabilities; FinTechs; General-purpose technology; Industry 4.0